2022
DOI: 10.1002/suco.202100544
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical study on shear behavior of strain‐hardening cementitious composite beams reinforced with fiber‐reinforced polymer bars

Abstract: Application of fiber-reinforced polymer (FRP) reinforcement in concrete beams may cause large deflection and crack width, as well as low shear capacity and ductility due to relatively small stiffness of FRP materials. To avoid these unfavorable factors and evaluate the shear behavior of FRP-reinforced structural members, a high-performance strain-hardening cementitious composite (SHCC) is introduced to substitute conventional concrete in reinforced beams, and four-point bending test is conducted in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/ undamaged concrete structures. [1][2][3][4][5][6][7][8] To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed. [9][10][11][12][13][14][15][16][17][18] Guo et al 19 found that a compressive strength model of FRP-confined undamaged concrete Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/ undamaged concrete structures. [1][2][3][4][5][6][7][8] To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed. [9][10][11][12][13][14][15][16][17][18] Guo et al 19 found that a compressive strength model of FRP-confined undamaged concrete Discussion on this paper must be submitted within two months of the print publication.…”
Section: Introductionmentioning
confidence: 99%